Association of the anti-angiogenic factor secreted protein and rich in cysteine (SPARC) with vascular complications among Chinese type 2 diabetic patients in Singapore - Moh, Mei Chung; Sum, Chee Fang; Tavintharan, Subramaniam; Pek, Sharon Li Ting; Yeoh, Lee Ying; Ng, Xiaowei; Lee, Simon Biing Ming; Tang, Wern Ee; Lim, Su Chi (Journal of diabetes and its complications, 2017)
This study evaluated the association of the anti-angiogenic SPARC with known angiogenesis-associated factors and diabetes-related micro- and macro-vascular complications in a Singapore Chinese cohort with type 2 diabetes (T2DM). Plasma SPARC was measured by immunoassay in 438 T2DM adults (mean age:58±11years). Higher SPARC levels in subjects stratified by SPARC tertiles displayed decreased pro-angiogenic adiponectin, osteopontin, vascular cell adhesion molecule (VCAM)-1 and matrix metalloproteinase (MMP)-2 concentrations (all p<0.05). The anti-angiogenic pigment epithelium-derived factor (PEDF) level was not statistically different among the SPARC tertiles. Age-adjusted partial correlation revealed significant associations of SPARC with adiponectin, osteopontin, VCAM-1, MMP-2, and PEDF (all p<0.05). Lower SPARC was accompanied by less favorable estimated glomerular filtration rate (eGFR) and carotid–femoral pulse wave velocity (PWV) readings (all p<0.05). Conversely, ankle–brachial index (ABI) reduced with increasing SPARC (p=0.048). The eGFR (B=0.834, p=0.019), PWV (B=−7.925, p=0.009), and ABI (B=−142.160, p=0.010) remained as determinants of SPARC after confounder adjustment. Moreover, individuals in the lowest SPARC tertile had increased odds of aortic stiffness (OR=1.900, 95% CI=1.103−3.274) but reduced odds of peripheral arterial disease (OR=0.400, 95% CI=0.175−0.919). However, SPARC was not independently associated with chronic kidney disease. The anti-angiogenic SPARC may be associated with the pathophysiology of diabetes-related macrovascular complications.